Spatial Differences in Stunting and Household Agricultural Production in South Africa: (Re-)Examining the Links Using National Panel Survey Data - Steffen Otterbach; Michael Rogan (Institute of Labor Economics (IZA), 2017)
South Africa is one of only a handful of countries in which the prevalence of child stunting has increased over the period during which progress towards the Millennium Development Goals (MDGs) has been monitored. One explanation for this reversal is that Big Food retail chains have been contributing to a low quality diet across the country, particularly in poor urban households. To examine this claim, we use nationally representative longitudinal data (2008–2014) to trace 6 years of stunting's evolution among South African children and adolescents aged 0–19, with particular attention to how the prevalence of stunting differs between urban (14.9%) and rural (19.6%) areas and how the drivers of poor nutrition vary spatially. The results suggest that, conditional on household income, subsistence farming is associated with a lower probability of stunting. Even more important, although under-nutrition retains a strong spatial component, once observable differences in living standards are controlled for, the higher tendency for children in deep rural households to suffer from (severe) stunting reverses.
Keywords: I14; I15; O15; O18; O55; 330; stunting; height for age; malnutrition; anthropometric measures; subsistence farming; nutritional inequality; South Africa